2023
DOI: 10.1111/gcb.16626
|View full text |Cite
|
Sign up to set email alerts
|

Shrinking body size and climate warming: Many freshwater salmonids do not follow the rule

Abstract: Declining body size is believed to be a universal response to climate warming and has been documented in numerous studies of marine and anadromous fishes. The Salmonidae are a family of coldwater fishes considered to be among the most sensitive species to climate warming; however, whether the shrinking body size response

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 93 publications
0
12
0
Order By: Relevance
“…Cheung et al (2013) suggested that half of the predicted 'shrinking' in maximum demersal fish body sizes could be driven by species redistributions, which are likely to be substantial. Since mean size relationships with temperature may be either positive or negative at the species-level (Audzijonyte et al, 2020;Solokas et al, 2023), decreasing mean body sizes within trophic guilds are likely to be largely influenced by changing species composition within trophic guilds. Another consideration is that we investigated temperature-body size relationships across space, and not in a fixed location over time.…”
Section: Discussionmentioning
confidence: 99%
“…Cheung et al (2013) suggested that half of the predicted 'shrinking' in maximum demersal fish body sizes could be driven by species redistributions, which are likely to be substantial. Since mean size relationships with temperature may be either positive or negative at the species-level (Audzijonyte et al, 2020;Solokas et al, 2023), decreasing mean body sizes within trophic guilds are likely to be largely influenced by changing species composition within trophic guilds. Another consideration is that we investigated temperature-body size relationships across space, and not in a fixed location over time.…”
Section: Discussionmentioning
confidence: 99%
“…Declines in species body size are among the main biological responses to climate change (McKenzie et al., 2021; Ohlberger, 2013; Pörtner & Peck, 2010; Scheffers et al., 2016; Sheridan & Bickford, 2011). Evidence for the emergence of climate‐driven trends toward shrinking body sizes remains, however, contentious (e.g., Audzijonyte et al., 2020; Huang, Ding, et al., 2021; Huss et al., 2019; Solokas et al., 2023). Here, based on analyses of scientific survey data gathered during the last three decades, we found a decline in the body size of anchovy in the Bay of Biscay.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, measuring fi sh lengths is low-effort and less expensive, and, as a result, length data are more widely available (Quinn and Deriso 1999 ). Length data are valuable in their own right by providing information on population size structure (Froese 2004 ;Mildenberger et al 2017 ) and long-term changes in body size resulting from environmental change (Oke et al 2020 ;Solokas et al 2023 ). Additionally, ages can be estimated from length and used to inform subsequent calculations (e.g., mortality).…”
Section: Introductionmentioning
confidence: 99%